By using properties of determinants, show that:

$\left|\begin{array}{lll}x & x^{2} & y z \\ y & y^{2} & z x \\ z & z^{2} & x y\end{array}\right|=(x-y)(y-z)(z-x)(x y+y z+z x)$

Vedclass pdf generator app on play store
Vedclass iOS app on app store

Let $\Delta=\left|\begin{array}{lll}x & x^{2} & y z \\ y & y^{2} & z x \\ z & z^{2} & x y\end{array}\right|$

Applying $R_{2} \rightarrow R_{2}-R_{1},$ and $R_{3} \rightarrow R_{3}-R_{1},$ we have:

$\Delta=\left|\begin{array}{ccc}x & x^{2} & y z \\ y-x & y^{2}-x^{2} & z x-y z \\ z-x & z^{2}-x^{2} & x y-y z\end{array}\right|$

$=\left|\begin{array}{ccc}x & x^{2} & y z \\ -(x-y) & -(x-y)(x+y) & z(x-y) \\ (z-x) & (z-x)(z+x) & -y(z-x)\end{array}\right|$

$=(x-y)(z-x)\left|\begin{array}{ccc}x & x^{2} & y z \\ -1 & -x-y & z \\ 1 & z-y & z-y\end{array}\right|$

Applying $R_{3} \rightarrow R_{3}+R_{2},$ we have:

$\Delta=(x-y)(z-x)\left|\begin{array}{ccc}x & x^{2} & y z \\ -1 & -x-y & z \\ 1 & z-y & z-y\end{array}\right|$

$=(x-y)(z-x)(z-y)\left|\begin{array}{ccc}x & x^{2} & y z \\ -1 & -x-y & z \\ 0 & 1 & 1\end{array}\right|$

Expanding along $R_{3},$ we have:

$\Delta=[(x-y)(z-x)(z-y)]\left[(-1)\left|\begin{array}{cc}x & y z \\ -1 & z\end{array}\right|+1\left|\begin{array}{cc}x & x^{2} \\ -1 & -x-y\end{array}\right|\right]$

$=(x-y)(z-x)(z-y)\left[(-x z-y z)+\left(-x^{2}-x y+x^{2}\right)\right]$

$=-(x-y)(z-x)(z-y)(x y+y z+z x)$

$=(x-y)(y-z)(z-x)(x y+y z+z x)$

Hence, the given result is proved.

Similar Questions

$\left| {\,\begin{array}{*{20}{c}}1&a&{{a^2}}\\1&b&{{b^2}}\\1&c&{{c^2}}\end{array}\,} \right| = $

If $a,b,c$ are unequal what is the condition that the value of the following determinant is zero $\Delta = \left| {\,\begin{array}{*{20}{c}}a&{{a^2}}&{{a^3} + 1}\\b&{{b^2}}&{{b^3} + 1}\\c&{{c^2}}&{{c^3} + 1}\end{array}\,} \right|$

  • [IIT 1985]

If $a, b, c$  are all different and $\left| {\,\begin{array}{*{20}{c}}a&{{a^3}}&{{a^4} - 1}\\b&{{b^3}}&{{b^4} - 1}\\c&{{c^3}}&{{c^4} - 1}\end{array}\,} \right|$ = $0$ , then the value of $abc(ab + bc + ca)$ is

If $\left| {\begin{array}{*{20}{c}}
  {{a^2}}&{{b^2}}&{{c^2}} \\ 
  {{{(a + \lambda )}^2}}&{{{(b + \lambda )}^2}}&{{{(c + \lambda )}^2}} \\ 
  {{{(a - \lambda )}^2}}&{{{(b - \lambda )}^2}}&{{{(c - \lambda )}^2}} 
\end{array}} \right|$ $ = \,k\lambda \,\,\left| {{\mkern 1mu} {\mkern 1mu} \begin{array}{*{20}{c}}
  {{a^2}}&{{b^2}}&{{c^2}} \\
  a&b&c \\
  1&1&1
\end{array}} \right|,\lambda \, \ne \,0$ then $k$ is equal to

  • [JEE MAIN 2014]

Evaluate $\left|\begin{array}{ccc}\cos \alpha \cos \beta & \cos \alpha \operatorname{csin} \beta & -\sin \alpha \\ -\sin \beta & \cos \beta & 0 \\ \sin \alpha \cos \beta & \sin \alpha \sin \beta & \cos \alpha\end{array}\right|$